Enteral nutritional strategy during therapeutic hypothermia: who? when? what? - Costa, Simonetta; Rizzo, Irene Del; Fattore, Simona; Serrao, Francesca; Priolo, Francesca; Corsello, Mirta; Tiberi, Eloisa; Tana, Milena; Catalano, Paola; Vento, Giovanni (Frontiers in Pediatrics, 2024)
Background: There are no guidelines regarding enteral feeding (EF) of infants with hypoxic ischemic encephalopathy (HIE) during and shortly after therapeutic hypothermia; consequently, clinical practice is, to date, still variable. The objective of this study is to assess whether a minimal EF strategy during therapeutic hypothermia may associated whit a shorter time to full EF in infants with HIE, and to identify the clinical variables that independently affect the time to full EF.Methods: A retrospective study from January, 1 2015 to June, 30 2022 was performed at the Neonatal Intensive Care Unit of the Fondazione Policlinico Universitario Agostino Gemelli, IRCCS in Rome, which compared infants with HIE who received minimal EF during therapeutic hypothermia with those who did not. Results: 78 infants received minimal EF during therapeutic hypothermia and 75 did not. Fed infants reached full EF significantly faster than unfed infants. They moreover received parenteral nutrition and maintained central venous lines for a shorter time. A multivariate analysis, taking into account the variable of clinical severity, confirmed minimal EF as an independent beneficial factor for reaching full EF in a shorter time, and mechanical ventilation and seizures as independent factors for longer time to full EF.Minimal EF during therapeutic hypothermia is associated with a shorter time to full EF in stable infants with HIE. Further prospective studies are needed to better define the enteral nutrition strategy for infants during therapeutic hypothermia, regardless of the severity of clinical conditions.